Implementasi Kearifan Lokal Bali Tri Hita Karana dalam Pembelajaran Sekolah Dasar di Bali: Implementasi Kearifan Lokal Bali Tri Hita Karana dalam Pembelajaran Sekolah Dasar di Bali - Supriani, Ni Made; Ida Bagus Putu Arnyana; I Wayan Suja (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2025)
The purpose of the study is to apply the application of Tri Hita Karana in elementary school learning. The research method is a literature review. The results of the study found eight articles containing the application of Tri Hita Karana in elementary school learning, in the study one type of classroom action research, two experimental studies and five types of development research. The conclusion in this study found classroom action research, experiments and development regarding Tri Hita Karana in elementary schools, where Tri Hita Karana can improve learning outcomes, attitudes, and character of students. It is recommended that further research can teach Tri Hita Karana with inclusive school research samples so that Tri Hita Karana-based learning can be carried out evenly.